VD_FINDINFO Décision / 2014 / 467 vom 6. März 2014 - VD Tribunal cantonal (2014)
RÉCUSATION, EXPERTISE PSYCHIATRIQUE, CITATION À COMPARAÎTRE, EMPÊCHEMENTEN GÉNÉRAL | 114 CPP (CH), 182 CPP (CH), 251 CPP (CH), 393 al. 1 let. a CPP (CH), 56 CPP (CH)